Perceived Value, Customer Satisfaction, and Customer Loyalty in Herbal Scrub Products - Windi Afriani; Terra Saptina Maulani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This research is motivated by a significant decline in sales of herbal products/jamu (herbal medicine) from PT Martina Berto Indonesia during the 2021–2024 period, as reflected in the 2024 annual report. This downward trend indicates issues related to customer satisfaction and loyalty, changes in consumer perceptions of the product, and increased competition from other herbal brands. The continued decline in sales in 2024, reaching IDR 95 million, indicates a serious challenge to the product's sustainability in the market. This study aims to examine the influence of perceived value on customer loyalty of Sariayu Herbal Scrub through customer satisfaction in Bandung City. This study employs quantitative methods, incorporating verification approaches. The data used in this study consist of primary and secondary data. The sample consisted of 115 respondents. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 4 software, and the sampling method applied was the sample size technique. The results of this study indicate that perceived value has a positive and significant influence on customer satisfaction, customer satisfaction has a positive and significant influence on customer loyalty, and perceived value has a positive and significant influence on customer loyalty. However, perceived value influences customer loyalty indirectly through customer satisfaction. These findings offer practical insights for companies to improve perceived value and customer satisfaction, key strategies to enhance customer loyalty, and maintain business sustainability.